The classification of material mechanical properties using non-destructive vibration technique - Intan Maisarah, Abd Rahim; Fauziah, Mat; Sazali, Yaacob, Prof. Dr.; Rakhmad, Arief Siregar (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/